The influence of innovation cluster on the contemporary Chilean foreign policy - Liudmila V. Diakova (Ибероамериканские тетради, 2017)
The article analyzes the in uence of innovation cluster on the contemporary Chilean foreign policy which has traditionally been pragmatic and aimed at promotion of national interests, attracting foreign investments and new technologies. The Chilean experience of cooperation with other countries in the field of innovation, the use of international agreements and regional blocs is a national variation of the maximum application of all opportunities to improve its competitiveness and sustainability in the modern world, to overcome the economic threats